Law No. 174 of the Year 2018 Dropping the Delay Charge, Surtax and Fines, Amending Some Provisions of Law No. 14 of the year 2018, and Re-enforcing Law No. 79 of the year 2016 Regarding Settlement of Tax Disputes = قانون رقم 174 لسنة 2018 بالتجاوز عن مقابل التأخير والضريبة الإضافية والغرامات وبتعديل بعض أحكام القانون رقم 14 لسنة 2018 بتجديد العمل بالقانون رقم 79 لسنة 2016 فى شأن إنهاء المنازعات الضريبية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic